2020
DOI: 10.1016/j.biopsych.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Traces of Trauma: A Multivariate Pattern Analysis of Childhood Trauma, Brain Structure, and Clinical Phenotypes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 84 publications
7
30
0
1
Order By: Relevance
“…This finding adds to previous research suggesting particularly detrimental effects of sexual and physical abuse on mental health of girls and women (Adams, Mrug, & Knight, 2018;Thompson, Kingree, & Desai, 2004). One reason for the distinct role of adversities may lie in the sex-specific effects they have on the nervous system, against the backdrop of sex differences in maturation, structure and functioning thereof (DeSantis et al, 2011;Dow-Edwards, 2020;Hodes & Epperson, 2019;Popovic et al, 2020). Moreover, characteristics of some risk factors have been shown to differ by sex: men are more likely to engage in more escalating and chronic patterns of cannabis use than women, for example (Hawes, Trucco, Duperrouzel, Coxe, & Gonzalez, 2019;Wagner & Anthony, 2007).…”
Section: Risk Factors Explaining Heterogeneity In Symptom Network Of Women and Mensupporting
confidence: 63%
“…This finding adds to previous research suggesting particularly detrimental effects of sexual and physical abuse on mental health of girls and women (Adams, Mrug, & Knight, 2018;Thompson, Kingree, & Desai, 2004). One reason for the distinct role of adversities may lie in the sex-specific effects they have on the nervous system, against the backdrop of sex differences in maturation, structure and functioning thereof (DeSantis et al, 2011;Dow-Edwards, 2020;Hodes & Epperson, 2019;Popovic et al, 2020). Moreover, characteristics of some risk factors have been shown to differ by sex: men are more likely to engage in more escalating and chronic patterns of cannabis use than women, for example (Hawes, Trucco, Duperrouzel, Coxe, & Gonzalez, 2019;Wagner & Anthony, 2007).…”
Section: Risk Factors Explaining Heterogeneity In Symptom Network Of Women and Mensupporting
confidence: 63%
“…Previous studies, including the largest study of childhood adversity to date ( 7 ), have demonstrated associations with smaller gray matter volume across a number of cortical regions ( 16 , 17 , 25 , 26 , 27 ). Our findings extend these prior associations by documenting that they encompass both surface area and cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying mechanisms through which adversity becomes biologically embedded and thereby disrupts development has been a vigorous focus of neuropsychiatric research ( 8 , 9 , 10 , 11 , 12 , 13 ). To date, research has revealed that childhood adversity is associated with alterations in the structural integrity of affective, motivational, mnemonic, and executive control networks ( 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ). However, the existing evidence for such biological embedding of adversity is limited in several ways.…”
mentioning
confidence: 99%
“…Diese neuen Trennlinien werden basierend auf maschinellen Algorithmen unter anderem anhand klinischer [39,40], kognitiver [41,42], genetischer [43][44][45], hirnfunktioneller [46][47][48] oder hirnstruktureller Muster [49,50] entworfen. Des Weiteren wurden bereits auch Kindheitstraumata [51], Psychopathie [52], Suizidalität [53] oder Empathie [54] mithilfe nicht-supervidierter Algorithmen in verschiedene neurobiologische oder genetische Merkmalsräume dekonstruiert.…”
Section: Diagnostikunclassified